KEEFEKTIFAN DAUN KOL DALAM MENGHAMBAT BENDUNGAN ASI PADA IBU MENYUSUI DI KLINIK BERSALIN BESNAWATI Br. SEMBIRING TAHUN 2019 - Sriyunita Perangin angin (Jurnal Maternitas Kebidanan, 2021)
Dams of breast milk in the mother's breast develop fever, pain, and inflammation. If not treated immediately, mastitis may occur. Mastitis in the mother's breast to the baby is not well nourished. The aim of this study was to minimize pain in the mother's breast against breast milk dams by using cabbage leaves in the Maternity Clinic of Besnawati Br. Sembiring and it is hoped that the mother will be able to face the postpartum period and the breastfeeding process well. This type of research is analytic with cross sectional study approach, namely by measuring several variables at once. The data analysis used in this research is qualitative and quantitative analysis. Quantitative analysis using the Chi-square statistical test. Types of data analysis were performed using the Statistical Package for the Social Science (SPSS) program computer, with a total sample of 30 people. Researchers are interested in finding a method that is more comfortable, can be done independently, and does not hurt the mother in overcoming breast engorgement, namely cabbage leaves, which have been shown to reduce swelling (ASI dam) in areas of the body that experience swelling, so it can be concluded that cabbage leaves can minimize pain in the mother's breast against breast milk dams by using cabbage leaves at the Maternity Clinic Besnawati Br. Sembiring and it is hoped that the mother will be able to face the postpartum period and the breastfeeding process well.